2016
DOI: 10.1177/2329488416633852
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Contradict and Standing Up for the Company: An Exploration of the Relationship Between Organizational Dissent, Organizational Assimilation, and Organizational Reputation

Abstract: This study explored relationships between organizational assimilation, organizational reputation, and organizational dissent. Survey data collection using standard instruments was conducted with a sample of employees drawn from three countries (the United States, the United Kingdom, and Australia). Analysis revealed that the expression of dissent to management and to coworkers was significantly and positively correlated with both organizational assimilation and organizational reputation. In particular, finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Third, the findings extended our understanding of the relationship between assimilation and articulated dissent (Croucher et al , 2019; Goldman and Myers, 2015) by adding mutual-face concern as the antecedent. The results suggest employees who have mutual-face concern are more likely to express articulated dissent through assimilation.…”
Section: Implications Future Directions and Limitationsmentioning
confidence: 52%
See 2 more Smart Citations
“…Third, the findings extended our understanding of the relationship between assimilation and articulated dissent (Croucher et al , 2019; Goldman and Myers, 2015) by adding mutual-face concern as the antecedent. The results suggest employees who have mutual-face concern are more likely to express articulated dissent through assimilation.…”
Section: Implications Future Directions and Limitationsmentioning
confidence: 52%
“…However, research has found organizational assimilation is significantly positively related to the frequency of upward dissent (Croucher et al , 2019; Kassing, 1997), implying more assimilated members in an organization are more likely to have better understanding of norms and attitudes of expressing dissent in organizations. Such organizational members tend to be more informative and reflective of previous dissent cases of other organizational members (Croucher et al , 2019). Thus, they become more strategic in choosing upward dissent strategies in terms of face mitigation and competency.…”
Section: Organizational Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the findings of theoretical and applied studies. An organization with a high reputation outperforms its rivals and seems more attractive in the eyes of stakeholders (Croucher, Zeng & Kassing, 2019;Fombrun & Shanley, 1990). In other words, a strong reputation towards an organization makes it more preferable by making it more attractive (Chauvin & Guthrie, 1994;Mohammed, 2019).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Lillis, 2001). In a situation of low agency, people may feel excluded from reading and writing certain text genres, or enforced to read and write, and respond with an attitude of non-compliance, opposition or resistance towards the controlling part (Croucher et al, 2019;Thelander & Åkerström, 2019;cf. Thomas & Hardy, 2011;Corely & Gioia 2004).…”
Section: Rq 3: How Do Professionals Express Experienced Degrees Of Agency In Relation To Digital Text Sharing?mentioning
confidence: 99%